Application of three‐dimensional power Doppler ultrasound in prenatal diagnosis - Chaoui, R.; Kalache, K. D.; Hartung, J. (Ultrasound in obstetrics & gynecology, 2001)
Objective To assess the fetal cardiovascular system using three‐dimensional power Doppler ultrasound (3D‐PDU) in normal and abnormal conditions during the second half of gestation. Subjects Forty‐five normal fetuses and 87 selected pregnancies with different abnormalities involving the vascular system were examined. Methods The following regions of interest were assessed: placental, umbilical, abdominal, renal, pulmonary and intracranial vessels together with the heart and great arteries. Equipment used was a commercially available HDI‐3000 and 5000 ultrasound system with integrated 3D‐Color Power Angio® software. Data acquisition was performed by the free‐hand technique. Images were reconstructed online. In pathological cases, a maximum of three attempts of 3D reconstruction was allowed to obtain the information needed. Results Satisfactory visualization of the fetal vascular system using 3D‐PDU could be achieved in normal pregnancies. The main difficulty during the learning curve was the optimization of the power Doppler image prior to 3D data acquisition. Despite good visualization conditions, the reconstruction of satisfactory images was only possible in 56 out of the 87 (64%) pregnancies with abnormal vascular anatomy. These were abnormalities of placenta and umbilical vessels (n = 26), intra‐abdominal and intrathoracic anomalies (n = 12), renal malformations (n = 9), central nervous system (n = 4) and cardiac defects (n = 5). The main reasons for the lack of information were fetal position and movements, overlapping with signals from neighboring vessels as well as technical limitations of the online system. Details and figures of the potential field of interest in prenatal diagnosis are presented. Conclusion The study shows that 3D‐PDU can be applied in prenatal diagnosis. The method enables the visualization of the main parts of the fetal vascular system under normal and pathological conditions. The main fields of interest are the same as those where color Doppler provides information with the exception of the fetal heart where a trigger system is still needed. Copyright © 2001 International Society of Ultrasound in Obstetrics and Gynecology